Simplicity as a feature of an organizational structure - Hopej-Kamińska, Magdalena; Zgrzywa-Ziemak, Anna; Hopej, Marian; Kamiński, Robert; Martan, Janusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Among the desirable features of an organizational structure is simplicity. Its opposite, i.e. complexity, expresses a lack of order and entanglement, which are the source of waste. Although the desire for the simplicity of a structural solution is not new, in recent years it has been more clearly emphasized. Therefore, Ashby’s law stating that variety has to be balanced by a different kind of variety, is questioned. The purpose of this article is to present the concept of simplifying an organizational structure. The concept of a simple organizational structure offered in this paper is the result of a thorough analysis of the literature on this topic. However, the views concerning the level of simple structure centralization were verified by means of a fractal calculus. The article presents the results of the study concerning the factors influencing the simplicity of the structural solution as well as the procedure of simplifying the organizational structure
Argumenta Oeconomica, 2015, Nr 1 (34), s. 259-276
Keywords: organizational structure; simplicity